In Search of Equilibrium : Estimating Equilibrium Real Exchange Rates in Sub-Saharan African Countries - Mongardini, Joannes (IMF Working Papers; Working Paper ;, 2007)
This paper presents a methodology to estimate equilibrium real exchange rates (ERER) for Sub-Saharan African (SSA) countries using both single-country and panel estimation techniques. The limited data set hinders single-country estimation for most countries in the sample, but panel estimates are statistically and economically significant, and generally robust to different estimation techniques. The results replicate well the historical experience for a number of countries in the sample. Panel techniques can also be used to derive out of sample estimates for countries with a more limited data set.